Successful implementation of remote video consultations for patients receiving home parenteral nutrition in a national UK Centre. Issue 4 (14th October 2019) - Cloutier, Anabelle; Bond, Ashley; Taylor, Michael Ian; Ablett, Joanne; Teubner, Antje; Farrer, Kirstine; Leahy, Gavin; Abraham, Arun; Lal, Simon
Abstract: Rationale: Our intestinal failure unit provides care for patients from a wide geographical area. Patients dependent on home parenteral nutrition (HPN) are routinely reviewed in the clinic at 3–6 monthly intervals. Between March 2008 and 2015, we noted a significant rise in the number of patients under our care, with an associated 51% increase in clinic appointments offered. We evaluated whether telemedicine would provide a strategy to reduce patients' need to travel while maintaining safe clinical standards. Methods: Implementation began in December 2015 via patient consultation and small tests of change. Clinical data were obtained from a prospectively maintained database. Remote video consultation discussions were carried out via internet video call service (Skype). An anonymous satisfaction questionnaire was offered to patients for completion following consultation. The number of miles saved by obviating the need to attend hospital was calculated for each patient. Results: During the study period, patients receiving HPN rose by 18% to 288. Twenty-five patients used telemedicine for HPN follow-up, three of these for follow-up with the psychologist. By avoiding hospital attendance, this saved a mean travel distance of 56.7 miles with a total of 18 346.6 cumulative miles saved. Sixty-three per cent of patients rated their satisfaction with the system at ≥90%, with a mean satisfaction of 85%. Eight per cent of the telemedicine cohort was admitted with an HPN complication, compared with an admission rate of 24% for the whole HPN cohort. One emergency admission was avoided. Conclusion: Telemedicine can obviate the need for clinic attendance in HPN-dependent patients, so reducing the need of individuals with chronic illness to travel while maintaining standards for follow-up.